(untitled) (Clinics, 2012)
Since the first laparoscopic adrenalectomy, the technique has evolved and it has become the standard of care for many adrenal diseases, including pheochromocytoma. Two laparoscopic accesses to the adrenal have been developed: transperitoneal and retroperitoneal. Retroperitoneoscopic adrenalectomy may be recommended for the treatment of pheochromocytoma with the same peri-operative outcomes of the transperitoneal approach because it allows direct access to the adrenal glands without increasing the operative risks. Although technically more demanding than the transperitoneal approach, retroperitoneoscopy can shorten the mean operative time, which is critical for cases with pheochromocytoma where minimizing the potential for intra-operative hemodynamic changes is essential. Blood loss and the convalescence time can be also shortened by this approach. There is no absolute indication for either the transperitoneal or retroperitoneal approach; however, the latter procedure may be the best option for patients who have undergone previous abdominal surgery and obese patients. Also, retroperitoneoscopic adrenalectomy is a good alternative for treating cases with inherited pheochromocytomas, such as multiple endocrine neoplasia type 2A, in which the pheochromocytoma is highly prevalent and frequently occurs bilaterally.